2016
DOI: 10.4172/2155-9880.1000429
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Coronary Ectasia is Associated with Impairment of Left Ventricular Myocardial Performance and Aortic Elastic Properties

Abstract: Aim: To investigate ventricular functions and tissue Doppler echocardiography-derived myocardial performance index and the elastic characteristics of the aorta in patients with coronary artery ectasia. Material and methods:42 patients with coronary artery ectasia ; mean age 56.9 ± 9.1 years and 26 subjects with angiographically normal coronaries; mean age 54.1 ± 6.9 years, were included in the study. All the subjects underwent echocardiography and tissue Doppler imaging to determine left ventricular diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Ozturk et al demonstrated that e′ in the septal mitral annulus was lower in their patient group than in subjects with normal coronaries. Mahmoud showed that the averaged value of e′ in the septal and lateral mitral annuli was lower in patients with CAE than in subjects with normal coronary arteries. However, Ceyhan et al demonstrated that a′ in the septal mitral annulus was lower in patients with CAE, whereas there was no statistically significant difference regarding e′ in the septal and lateral mitral annuli.…”
Section: Discussionmentioning
confidence: 99%
“…Ozturk et al demonstrated that e′ in the septal mitral annulus was lower in their patient group than in subjects with normal coronaries. Mahmoud showed that the averaged value of e′ in the septal and lateral mitral annuli was lower in patients with CAE than in subjects with normal coronary arteries. However, Ceyhan et al demonstrated that a′ in the septal mitral annulus was lower in patients with CAE, whereas there was no statistically significant difference regarding e′ in the septal and lateral mitral annuli.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried by Triantafyllidi et al (31) on 40 patients with CAE; left ventricular end-diastolic diameter (LVEDD), LV mass and LV mass index were significantly increased in CAE group compared to control group. However, in a study carried by Mahmoud et al (23) , there was no significant difference in the values of LA, LVEDD, LVESD, PW, IVS and LVEF between the two groups. Although, the values of LVEDD were higher in CAE group (47.5 ± 8.6 mm) than the control group (45 ± 4.9 mm) and the LVEF was lower in CAE group (58.5 ± 7.8%) than the control group (61.6 ± 5.2%) but this was statistically insignificant.…”
Section: Discussionmentioning
confidence: 80%
“…Pulsed-wave tissue Doppler imaging and the myocardial performance index (MPI) have both showed that left ventricular (LV) diastolic function is decreased in individuals with CAE (23) . Two-dimensional STE has been applied to assess LV function in many conditions such as the coronary artery disease and coronary slow-flow phenomenon (24) .…”
Section: Introductionmentioning
confidence: 99%
“…showed that eʹ in the septal mitral annulus decreased compared with the control group. In a recent study, Mahmoud showed that the averaged value of eʹ in the septal and lateral mitral annuli was reduced in patients with CAE compared with the control group. However, Ceyhan et al .…”
Section: Discussionmentioning
confidence: 98%
“…Perturbation of the coronary flow and diseased microvasculature are possible pathophysiological mechanisms for myocardial ischemia in patients with CAE . It has been shown that left ventricular (LV) diastolic function is impaired in patients with CAE as demonstrated by pulsed‐wave tissue Doppler imaging in limited LV segments . Nonetheless, this method is angle‐dependent and susceptible to cardiac translational motion and tethering of the adjacent segments .…”
Section: Introductionmentioning
confidence: 99%